2023
DOI: 10.1007/s41042-022-00084-0
|View full text |Cite
|
Sign up to set email alerts
|

Hope that Benefits Others: A Systematic Literature Review of Hope Theory and Prosocial Outcomes

Abstract: This systematic literature review serves to illuminate the state of research that examines empirical evidence of hope and other-oriented variables (i.e. benefit individuals other than those who are being measured in the included studies). Thirteen articles were eligible for inclusion after the screening process and snowballing. Hope was positively related to variables such as social support seeking, altruism, community and social participation, and acting in favor of helping others. Data from the included stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…This relationship might differ based on how domain-general hope is assessed. The studies here used Snyder’s trait hope index which other work has shown correlates with pro-social behavior (see Schornick et al, 2023 for a systematic review), however, it is possible that other measures of domain-general hope might better align more strongly with climate engagement. Finally, future research should explore the effects of highlighting possibility of climate action yielding co-benefits (e.g., job creation, social justice, and positive health implications of the energy transition) rather than the potential to preserve the status quo.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship might differ based on how domain-general hope is assessed. The studies here used Snyder’s trait hope index which other work has shown correlates with pro-social behavior (see Schornick et al, 2023 for a systematic review), however, it is possible that other measures of domain-general hope might better align more strongly with climate engagement. Finally, future research should explore the effects of highlighting possibility of climate action yielding co-benefits (e.g., job creation, social justice, and positive health implications of the energy transition) rather than the potential to preserve the status quo.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study is to investigate the impact of human capital, hope, and work engagement on task performance in Indonesian manufacturing companies. To achieve this, we integrated human capital theory (Klein, Becker, & Meyer, 2012) and hope theory (Snyder, 2002;Schornick et al, 2023) with task performance theory, using work engagement theory as a direct mechanism and Conservation of Resources (COR) theory (Hobfoll, 1989) as an overarching framework. Our results confirm that human capital and hope are important employee resources that not only positively affect work engagement but also enhance it, leading to improved task performance.…”
Section: Discussionmentioning
confidence: 99%
“…in difficult situations. These beliefs become activated as thoughts and accompany goal-oriented activities [10][11][12][13][14][15][16][17]. Snyder's concept of hope concerns hope for success as it refers to one's belief that one will succeed and that this success will be the result of one's own competences [15].…”
Section: Introductionmentioning
confidence: 99%